KEKERASAN TERHADAP PEREMPUAN DALAM RELASI PERNIKAHAN SIRRI - Saeroni, Saeroni; Andari, Indiah Wahyu (Sunan Kalijaga State Islamic University & The Asia Foundation, 2013)
This paper discusses the dynamics of violence against women in informal maritalÂ relations based on the experience and institutional data of RifkaAnnisa Yogyakarta. This paper will discuss the characteristics of victims and perpetrators in informal marriages, the dynamics of violence experienced by victims and the factors behind informal marriages. This research will affirm that all women who are victims of violence in informal and polygamous marriages experience physical, sexual, economic and emotional violence. The myth that second wives or young wives are pampered compared to first wives is disproved here. Even though it may happen occasionally, they are still at risk of economic violence. The most common form of economic violence are in the forms of abandonment or forcing their wives to work. Informal marriage and polygamous marriages continue to happen due to several conducive factors, among them: the low legal awareness of victims and lack of legal sanctions for perpetrators of informal marriages, the view that religion opens the possibility for informal marriages, the social paradigm which strengthens the superiority of men over women, family support and societyâ€™s permissiveness to informal marriages and the ongoing violence against women.